Breast Cancer Detection Using Deep Belief Network by Applying Feature Extraction on Various Classifiers - et. al., Prasath Alias Surendhar S, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Among various types of cancer, breast cancer is considered as second largest hazardous diseases that cause death. Initially, small lump like structure grow from breast cells which are considered as malignant lumps. To find the available of malignancy in breast area, several checkups such as self-test and periodic has to be done to reduce the death rate due to breast cancer. But, the classification of breast cancer by medical physicians using available techniques is not sufficient, so it is important to improve the classification technique using neural network. The four important phases namely preprocessing, segmentation, feature extraction, and classification can be done in constructed Deep Belief Network (DBN) whereas preprocessing makes to remove the noise and artifacts of mammogram image and then the glands are enhanced. The preprocessed output is given to fuzzy c-means segmentation process with the help of masking. Again the feature extractors such as Scale Invariant Feature Transform (SIFT) and Speeded up Robust Transform (SURF) made to apply on two types of classifiers such as gradient boosting tree classifier and adaboost classifier. The examination is done interms of parameters such as accuracy, precision, recall and F1 score.